A crystallographic study on luminescent group 13 and selected lanthanide trivalent metal complexes - Alexander, Orbett T. (University of the Free State, 2015)
The aim of this project is to try and understand the solid and solution state chemistry crystallography and NMR techniques to correlate the results thereof with the luminescence characteristics of the M(N,O)3 complexes as described below and that was led by the prime solid state factors that hugely influences the luminescence characteristics differently than in the liquid state. Four complexes of the type M(N,O)3 [M = Al, Ga, In. N,O = bidentate quinolinol type ligands: Ox = 8-hydroxyquinoline, 57dmOx = 5,7-dimethyl-8-hydroxyquinoline, 57dcOx = 5,7-dichloro-8-hydroxyquinoline] were synthesized. The obtained complexes were characterized by single crystal X-ray diffraction as well as other spectroscopic techniques (NMR, PL and UV-Vis) and includes the formation of the following mer-[Al(Ox)3]∙EtOH, mer-[(Ga(Ox)3]∙0.5∙EtOH, mer-[(Ga(57dmOx)3]∙0.5∙DCM, mer-[In(Ox)3]∙2H2O.Two more complexes of type Ln(N,O)3 [Ln = Europium, N,O = 5,7-dichloro-8-hydroxyquinoline] which are [Eu(57dcOx)3]·EtOH·H2O and κ2-O,O’-[Eu(57dcOx)3·EtOH]. The NMR solution studies gave some understanding with regard to the facial and meridional conformation of the complexes. The crystal structures of mer-[Al(Ox)3]∙EtOH, mer-[(Ga(Ox)3]∙0.5∙EtOH, and mer-[In(Ox)3]∙2H2O, crystalizes in the same crystal system (monoclinic), space group (P21/n) and contain four number of molecules in the unit cell. That of mer-[(Ga(57dmOx)3]∙DCM crystallized in the triclinic crystal system (P ̅) with two molecules in the unit cell. Complex : [Eu(57dcOx)3]·EtOH·H2O and κ2-O,O’-[Eu(57dcOx)3·EtOH] crystallized in a trigonal and triclinic crystal system in space group R ̅ and P1 respectively. Photoluminescence measurements were done on all the synthesized complexes. Change in intensity behaviour was observed as an influence of the metal and/or the ligand substitutions. The wavelength shifts were observed as a result of metal influence and also the influence from the geometrical conformation of the complexes (mer- or fac-).
Keywords: Aluminium; Gallium; 8-hydroxyquinoline; Fluorescence; Oleds; Meridional; Facial; Photoluminescence (PL); Metal complexes; Thesis (M.Sc. (Chemistry))--University of the Free State, 2015